CONCEPTUALIZATION OF RISK MANAGEMENT IN THE CORPORATE GOVERNANCE SYSTEM OF MULTINATIONAL ENTERPRISES (Вісник: Міжнародні відносини, 2024)
The purpose of the article is to summarize and present the fundamental trends of the last decade related to the formation of the role and place of risk management in the system of corporate governance of multinational enterprises (MNEs).The analysis is based on the latest research by leading international researchers, such as American scientists Warren Bennis, Bert Nanus, Hugh Grove and Lorenzo Patelli, British scientists Mingzhui Wang, Elizabeth Kelan and Kevin Crowley, international organizations Basel Committee on Banking Supervision, Group of Thirty, Institute of international finance and the Organization for Economic Cooperation and Development. The conducted analysis clearly indicates that failures in MNEs risk management over many years led to catastrophic losses in various industries, when such failures, as in the energy sector, led not only to financial, but also to significant environmental consequences. Among the most significant incidents, we can highlight the accidents on the oil platform "Deepwater Horizon" of the British oil and gas company BP in 2010 in the Gulf of Mexico and the Japanese nuclear power plant Fukushima-1 in 2011. Often these failures also contributed to failures in corporate governance, where boards of directors did not fully consider the risks that MNEs were taking and/or imperfect risk management systems.Thus, the conceptualization of risk management in the system of corporate governance of MNEs becomes an important component of achieving medium and long-term strategic goals of MNEs in conditions of growing macroeconomic and geopolitical uncertainty.
Keywords: risk management, corporate governance